Limit theorems for oscillatory functionals of a Markov process - Androshchuk, T.O.; Kulik, A.M. (Інститут математики НАН України, 2005)
We study the limit behavior of a family of functionals from a given Markov process which are called oscillatory functionals. The typical oscillatory functional is homogeneneous and non-negative but neither additive nor continuous. We claim that the discontinuity and non-additivity of functionals from a given family vanish in the limit and, in this framework, prove a generalization of the theorem by E.B. Dynkin on the convergence of a family of W-functionals.